Specific-heat Study of Low-energy Vibrational State m Vitreous Samarium Phosphates - Hassan, Senin; Abd. Aziz, Sidek; G. A., Saunders; G., Carini (Universiti Putra Malaysia Press, 1995)
Measurements of specific heat in the temperature range 1.5K to 30K were made for two samples of vitreous samarium phosphates. A large contribution to the specific heat, well above what is expected from acoustic phonons (in the Debye approximation), is discussed in terms of the theoretical predictions of a phonon-fracton cross-over approach. The phonon-fracton density of states used to fit the excess specific heat gives rise to model parameters with the same magnitudes as those found previously for a wide range of glasses.